Unmet care needs of older individuals: prevalence, patterns and influencing factors - Kohanová, Dominika; Tomciková, Mária; Solgajová, Andrea (Magyar Gerontológia, 2024)
Understanding and identifying unmet needs are crucial for improving the quality of health and social care. Research addressing unmet needs among older individuals in Slovakia is insufficient, highlighting the need for further investigation into this pressing issue.